The Character Education Strengthening Management: Multiple-Case Study in Senior High School - Panoyo, Panoyo; Riyanto, Yatim; Handayaningrum, Warih; Tunik Muharlisiani, Lusy; Noerhartati, Endang (Opción, 2019)
This study aims to describe and analyze data about the management of char- acter education strengthening in Sidoarjo Regency of Indonesia with a mul- ti-case study in Senior High School. The qualitative approach using to analysis that emphasizes the meaning and understanding of the inside (verstehen), rea- soning, definition of a particular situation (in certain contexts) in the case in the Implementation of Character Education in Sidoarjo Regency. The manage- ment component starts with planning, organizing, implementing, monitoring, and evaluating the strengthening of character education. The management of character education strengthening in Sidoarjo regency indicates that planning for character education must meet at least five aspects. Organizing in charac- ter education strengthening is done with four aspects. The implementation of character education strengthening there is six main components. Supervision of the strengthening of character education there are four main components. However, the resulting study reveals that there are four main components in evaluating character education, including the preparation and manufacturing of assessment instruments, carried out by internal and external parties, pro- ducing factors that influence the program, and requiring follow-up to make continuous improvements.